Language and Social Cover: The Cultural Evolution of the Theory of Mind - Fernández Castro, Víctor (Analysis. Journal of Philosophical Research, 2020)
Recently several views in cognitive sciences and philosophy have argued that human capacity to ascribe mental states to predict and explain human behavior is a product of cultural evolution; that is, its emergence is not the product of the selection of genetically inherited structures but the product of hereditary variation through mechanisms of social learning.  The aim of this article is to propose a model of the theory of mind as a linguistic mechanism of social cover and reputation management within the framework of cultural evolution. This position, called The Social Cover Model, is presented and defended in contrast to three other positions that will be critically evaluated. Finally, the model of two possible objections will be defended.